EVIDENCE FOR CONTROL OF THE RATE OF NUCLEAR DNA SYNTHESIS BY THE NUCLEAR MEMBRANE IN EUKARYOTIC CELLS - Alfert, Max (1969)
Rates of DNA synthesis in root tip cells of diploid and autotetraploid snapdragon (Antirrhinum majus) seedlings and in diploid and tetraploid (mononucleate and bidiploid-nucleate) regenerating mouse-liver cells have been studied. The increase in this rate in the tetraploid cells is closely correlated with the increase in nuclear surface area, but not with the nuclear volume; this suggests a possible control of the rate of DNA synthesis by the nuclear membrane.